Comparison of science performance among male and female Iranian eighth grades students. - Sahranavard, Maryam; Hassan, Siti Aishah (Progressive Science Publications, 2013)
The main objective of the present study is to explore the comparison of male and female science performance. The participants in the study consisted of 680 lower secondary school children, 14 year olds (317 male and 363 female) at Tehran and Shahriar city, the province of Tehran, Iran. The research design was an ex-post facto and tested the alternative hypothesis. The students’ science performance which measured by the report school test was used to assess science performance. Descriptive statistics, and to compare male and female students in science performance ANOVA was used. The results showed that there is no significant difference between male and female students in science performance. This study supports the new findings that girls perform better than boys in science subject and has resulted in larger mean score in girls in science performance rather than boys.